Application of Apatite EPMA Analyses in the Haftcheshmeh Cu-Mo Porphyry System as a Chemical Indicator of the Source Magma - Shohreh Hassanpour; Maryam Ahankoub (Journal of Economic Geology, 2024)
The Haftcheshmeh Cu-Mo porphyry system is located in the Arasbaran magmatic zone in Alborz-Azarbaijan structure zone, northwestern Iran. As ore mineralization occurred mainly in gabbrodiorite and granodiorite porphyry stocks, chemical compositions of rock forming minerals in gabbrodiorite and granodiorite porphyries are used to identify critical vectors of magmatic processes and hydrothermal mineralization related to the formation. All analyzed (magmatic and hydrothermal) apatites saturation temperatures show ranges of calculated temperatures of 830°C to 877°C and pressures of 0.11 to 0.96 Kbar, corresponding to depths of 4 to 10 km and H2Omelt content (3< wt.%), and suggesting a hydrous calc-alkaline magma generated from a deep magmatic source. Analyzed apatite support the ore forming magmas which are oxidized by I type magma with relatively high ƒO2. The trend of volatile element variations indicated that primary fluid exsolution probably occurred at temperatures from ~712°C to 842°C and was affected by hydrous and oxidized mafic magma from a deeper part of the magma reservoir. It may result in an extensive magma mixture with fractional crystallization of apatite in the evolved gabbrodiorite and granodiorite magma chambers.